2021
DOI: 10.15448/1984-7289.2021.2.35559
|View full text |Cite
|
Sign up to set email alerts
|

Políticas da toxicidade

Abstract: Este artigo analisa as estratégias e hipointervenções utilizadas pelos moradores da Fercal, no Distrito Federal, Brasil, para lidar com a presença ubíqua, desigual e contínua da poluição do ar por partículas totais em suspensão (PTS), derivada da atuação de duas fábricas de cimento locais, a Votorantim Cimento e a Cimento Planalto (Ciplan). A pesquisa foi operacionalizada através da realização de 30 entrevistas semi-estruturadas, entre os anos de 2017 e 2018. Levando em consideração o caráter lento e contínuo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…However,Lamichhane et al (2021) find this relation between exposure to pollution and prenatal maternal stress in South Korea, as doZhang et al (2021) in university students in China. Although efforts to study the effect of pollution on negative emotions in Latin America have been made, these studies have been mainly linked to emotions like «annoyance»(Melo et al 2015, Machado et al 2018, 2020, added to sporadic efforts on other emotions(Boso et al 2019, Bertanha 2021). Yet this review found no studies on emotions such as fear, blame or hopelessness, as in other countries like the United States(Lal et al 2020) or China(Xue et al 2019).…”
mentioning
confidence: 99%
“…However,Lamichhane et al (2021) find this relation between exposure to pollution and prenatal maternal stress in South Korea, as doZhang et al (2021) in university students in China. Although efforts to study the effect of pollution on negative emotions in Latin America have been made, these studies have been mainly linked to emotions like «annoyance»(Melo et al 2015, Machado et al 2018, 2020, added to sporadic efforts on other emotions(Boso et al 2019, Bertanha 2021). Yet this review found no studies on emotions such as fear, blame or hopelessness, as in other countries like the United States(Lal et al 2020) or China(Xue et al 2019).…”
mentioning
confidence: 99%